The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.21037/apm-20-1339
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives of people accompanying a person during voluntary stopping eating and drinking: a convergent mixed methods study

Abstract: Background: Voluntary stopping eating and drinking (VSED) is an option for people wishing to bring about premature death. In Switzerland, VSED is considered a controversial action at the end of life in the guidelines for "Management of dying and death," which states that the decision to support or oppose VSED must be made individually by health care professionals; so far there are no instructions for action. The aim of this research was to explore the experiences of people who play an important role in VSED ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…There is an increasing call for clinical guidelines for professional caregivers in different countries, similar to the Dutch and American guidelines. 7,[32][33][34] In our study, we found a need for guidance among patients and relatives as well. It is important that professional and patient guidelines apply to the full spectrum of patients considering VSED.…”
Section: Practical Implicationsmentioning
confidence: 91%
“…There is an increasing call for clinical guidelines for professional caregivers in different countries, similar to the Dutch and American guidelines. 7,[32][33][34] In our study, we found a need for guidance among patients and relatives as well. It is important that professional and patient guidelines apply to the full spectrum of patients considering VSED.…”
Section: Practical Implicationsmentioning
confidence: 91%
“…Constructivist researchers acknowledge that data, analyses and methodological strategies are constructed and take into account the research context and the perspectives of researchers in their interpretations [ 55 ]. The grounded theory was underpinned by a pragmatic philosophical perspective, which assumes that our knowledge is developed through our actions and interactions, which are shaped and developed by our social environment [ 57 , 58 ]. Since the phenomenon under investigation in this study was little known internationally at the time of the investigation and had not been researched in Switzerland until then, the recruitment of participants was challenging, which is why theoretical sampling as an instrument of theoretical saturation could not be implemented in this research.…”
Section: Methodsmentioning
confidence: 99%
“…This study is a research strand integrated in a convergent mixed method [ 59 ], which was pre-recorded in a study protocol. [ 60 ] Since at this stage the mixed-methods study could already be published [ 58 ], there are some overlaps in the description of the method. However, the method had to be greatly shortened in mixed-methods article, so that the same contents had to be taken up in this paper, but described in more detail for better comprehensibility.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation